Tobacco smoking and cancer: The promise of molecular epidemiology - WANG SOPHIA S; SAMET JONATHAN M (Instituto Nacional de Salud Pública, 1997)
Neoplasic development is a multistage process that includes multiple genetic changes. In this article the authors review studies on molecular epidemiology of tobaco. Current concepts of the multistage carcinogenic model are reviewed, as are their use in observational studies. Finally, benzo[a]pyrene are analyzed as an example.